(untitled) (International Journal of Engineering and Computer Science, 2025)
In this paper, we defined operations on Pythagorean fuzzy ideals and the Pythagorean fuzzy ideal of a Pythagorean fuzzy lattice is introduced. Certain characterizations of these are provided. The residuals of Pythagorean fuzzy ideals are defined, and it is demonstrated that these residuals also form Pythagorean fuzzy ideals. Furthermore, it is shown that they are the largest Pythagorean fuzzy ideal of P .